High spirits : the comic art of Thomas Rowlandson - Rowlandson, Thomas; Belloli, Andrea; Belloli, Andrea (Royal Collection Trust, 2013)
The absurdities of fashion, the perils of love, political machinations and royal intrigue were the daily subject matter of Thomas Rowlandson, one of the leading caricaturists of Georgian England. Rowlandson was working at a time when English satirical prints were prized by collectors across Europe. A number of the works in the exhibition were purchased by George, Prince of Wales, later Prince Regent and King George IV. Ironically the Prince was often the butt of caricaturists' jokes and sometimes tried to prevent the publication of images that he felt were particularly offensive. Through Rowlandson's drawings and prints, the exhibition examines life at the turn of the 19th century. 0Exhibition: The Queen's Gallery, Palace of Holyroodhouse, Edinburgh, UK (11.2013)